For some rational function f(x), the graph of y=f(x) has an oblique asymptote of y=5x+7. Enter the equation of the horizontal asymptote of the graph of
Might be continued here
If f(x) were a function like: f(x) = (5x2 + 2x + 8) / (x - 1) it would have an oblique asymptote of y = 5x + 7.
This would make the final function: y = [ (5x2 + 2x + 8) / (x - 1) ] / (x - 2)
and would simplify to: y = (5x2 + 2x + 8) / [ (x - 1)(x - 2) ]
or: y = (5x2 + 2x + 8) / (x2 - 3x + 2)
which would have an horizontal asymptote of y = 5.
Now, this is just an example, but I believe that this would be true for all examples, so the equation of the horizontal
asymptote woulld always be: y = 5.